Escrevivência Fronteiriça: corpogeografias de vida - Viviani Cavalcante de Oliveira Leite (2025)
This thesis develops an epistemic-conceptual theorization based on the concept of Escrevivência, coined by Conceição Evaristo, expanding it into a border perspective as a decolonial epistemic practice, articulating the dimensions of being, knowing, and method in knowledge production from the borders of the modern/colonial world-system. The research is structured in three fundamental axes corresponding to its central chapters. The first chapter traces a genealogy of the coloniality of being, establishing connections between the historical persecution of dissident bodies - from the European stake to Brazilian colonization - and proposing border escrevivência as a practice of epistemic disobedience through the inclusion of corpogeographies of life in the production of academic knowledge. The second chapter develops a reflection on the epistemologies of exteriority, contrasting the colonial imaginary world with the border life-world, and articulates the concepts of sentipensar and own thinking to ground the praxis of the border epistemic writing body. The third chapter presents the grammar of border escrevivência as an insurgent methodology, grounded in the ethics of delinking and in the articulation between body-politics and geopolitics of knowledge, culminating in the continued development of the theorization of corpogeographies of life, the sixth sense, as an expression of this methodological practice. The research stems from a border biographical critical epistemology, as it thinks from specific loci and bodies, anchored mainly in Walter Mignolo's decolonial theories and Edgar Cézar Nolasco's theoretical reflections. The investigation maintains that border escrevivência, emerging from bodies marked by colonial ontological difference, subverts the fundamental strategy of the modern/colonial project: the epistemic exclusion of bodies and their consequent disembodiment in knowledge production. As research limitations, it is acknowledged that the very nature of the work, in proposing an emergent and situated methodology, faces the challenge of its validation within traditional academic frameworks. Furthermore, the breadth of border experiences and the diversity of geopolitical contexts cannot be fully contemplated in a single study, suggesting the need for future investigations to expand and deepen the propositions presented here. Keywords: Border Escrevivência; Corpogeographies of life; Decoloniality; Epistemologies of exteriority; Grammar of border escrevivência.